2015
DOI: 10.5799/ahinjs.01.2015.03.0520
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid surgery: comparison between ultrasonic scalpel-SonoSurg and classic clamp and tie technique

Abstract: Objective:The purpose of this prospective study was to evaluate the efficacy and safety in the application of ultrasonic scalpel compared to conventional operative technique in open surgery of the thyroid gland. Methods:The study included 100 patients operated between May 2013 and August 2013. Patients were divided into two groups -50 patients were operated using So-noSurg® and 50 patients were operated using classic "clamp and Tie" technique. We evaluated and compared the outcome between the two groups.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
2
1
0
Order By: Relevance
“…Hematoma developed postoperatively in four patients in this study; two of them required urgent surgical intervention to evacuate hematoma and secure hemostasis (one in each hemostatic group), two patients were treated conservatively (statistically not significant). This result is similar to the result of Cannizaro MA et al 2 , Ali SM et al 9 , and Vidinov KN et al 10 but differs from result found by Ecker T et al 8 study which showed a decrease in the incidence of post-operative hematoma by using harmonic scalpel for hemostasis In the present study, four patients developed hypocalcemia postoperatively and were treated by calcium supplement and all the cases were temporary and recovered within six months. Length of hospital stay was not affected by type of hemostasis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Hematoma developed postoperatively in four patients in this study; two of them required urgent surgical intervention to evacuate hematoma and secure hemostasis (one in each hemostatic group), two patients were treated conservatively (statistically not significant). This result is similar to the result of Cannizaro MA et al 2 , Ali SM et al 9 , and Vidinov KN et al 10 but differs from result found by Ecker T et al 8 study which showed a decrease in the incidence of post-operative hematoma by using harmonic scalpel for hemostasis In the present study, four patients developed hypocalcemia postoperatively and were treated by calcium supplement and all the cases were temporary and recovered within six months. Length of hospital stay was not affected by type of hemostasis.…”
Section: Discussionsupporting
confidence: 90%
“…The conventional hemostasis technique uses knot and tie so can consume time. On the other hand, using the electrocautery in thyroid surgery can also cause adjacent nerves and parathyroid glands injury due to distal thermal effect 2,4,10 , therefore, the need for secure hemostasis with less time consuming becomes crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Post-operative hematoma was observed in one patient from the conventional group, necessitating urgent intervention. These findings correspond with those of Govindaraj M. et al [15] , Challa S et al 2012 [20] , and Vidinov KN et al [21] , but differ from Ecker T et al [19] , which noted a reduced hematoma incidence when using electrosurgery for hemostasis.…”
Section: Discussionsupporting
confidence: 89%